Composting of Aged Reed Bed Biosolids for Beneficial Reuse: A Case Study in New Jersey, USA. Issue 4 (1st October 2016) - Kannepalli, Sarat; Ravit, Beth; Strom, Peter F.
ABSTRACT: Reed beds with Phragmites australis (common reed) have been utilized to decrease the water, nutrient, and volatile solids content of sewage sludge. An efficient disposal/reuse option was sought for reed bed biosolids accumulated over a 15-year period at a wastewater treatment facility in New Jersey, USA. The study facility had 14 reed beds, each with 1000 wet tons capacity, which were full, and so the solids needed to be removed. Because P. australis is considered an invasive species in New Jersey and several other states in the United States, disposal or reuse of solids containing this plant is regulated. Composting was examined as a potential treatment for destroying the plant's reproductive rhizomes. The high temperatures achieved during composting were also tested to determine if regulatory criteria for pathogen reduction could be met, making the composted product suitable for unrestricted land application. Preliminary studies indicated the sludge had stabilized to the point where self-heating did not occur. Among the carbon amendments tested in the laboratory to stimulate compositing activity, Phragmites above-ground biomass was determined to be most suitable. In a field test, Phragmites above-ground biomass was mixed with reed bed biosolids at a 1:2 (w/w) ratio. The temperatures achieved resulted in complete mortality of Phragmites rhizomes. In laboratory tests, rhizomes placed in a drying oven at 50°C for 24 h, or 55°C for 12 h, showed 100% plant mortality. However, under field conditions pile temperatures could not be maintained long enough for the sludge to meet the USEPA 503 biosolids time-temperature pathogen rule requirements for unrestricted land application, even though sample fecal coliform counts did meet regulatory limits.